PL002: A randomized controlled trial on oral analgesic utilization for children presenting with a musculoskeletal trauma in the emergency department. (2nd June 2016) - Le May, S.; Ali, S.; Plint, A.; Mâsse, B.; Neto, G.; Auclair, M.; Gouin, S.
Abstract : Introduction: Background: A single-agent approach to children's moderate to severe pain is often inadequate. To date, no studies have evaluated the combined use of oral morphine and ibuprofen for optimal pain management of children presenting to an Emergency Department (ED) for musculoskeletal (MSK) trauma. Objective: To assess the efficacy of a combination of oral morphine and ibuprofen for pain management in children with MSK trauma in the ED.Methods: A double-blind, placebo-controlled, multi-centered, three-arm, randomized clinical trial of 500 patients was conducted at three pediatric tertiary care EDs. Patients 6 to 17 years of age, who presented to the ED with a MSK trauma, and a score >30 mm on the 100 mm Visual Analogue Scale were eligible to participate. Patients were randomized (in a 2:1:1 ratio) to receive (orally): (a) morphine (0.2mg/kg) + ibuprofen (10mg/kg) (Group MOR + IBU) or (b) morphine (0.2 mg/kg) + placebo (Group MOR) or (c) ibuprofen (10mg/kg) + placebo (Group IBU). Primary outcome was pain intensity score under 30 mm (mild pain) at 60-minutes (T-60) after treatment administration.Results: A total of 456 patients were included in analyses: 177 (MOR + IBU), 188 (MOR), 91 (IBU). Mean age was 11.9 + 2.7 years, with a majority of boys (55.3%) and soft tissue injuries (62%). There were no differences in baseline characteristics in the three groups. Baseline mean pain score was 60.9 + 16.2 mm. Only 30% (MOR + IBU), 29% (MOR) and 30% (IBU) of patients reached a pain score under 30 mm at T-60 (p=0.83). Mean pain scores at T-60 were 42.3 + 23.2 mm (MOR + IBU), 43.8 + 23.1 mm (MOR) and 42.3 + 23.3 mm (IBU) (p=0.83). No severe adverse events were observed in any of the groups, at any of the study measurement points.Conclusion: Combination of morphine with ibuprofen did not provide any additional pain relief for children with MSK injuries, in the ED. None of the study medication provided optimal pain management, as the majority of children did not reach the WHO definition of mild pain. Alternative analgesic combinations should be investigated to optimize pain relief of children who present to the ED with MSK injuries.